2016
DOI: 10.1007/s13524-016-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

The (Conditional) Resource Dilution Model: State- and Community-Level Modifications

Abstract: One of the most consistent patterns in the social sciences is the relationship between sibship size and educational outcomes: those with fewer siblings outperform those with many. The resource dilution (RD) model emphasizes the increasing division of parental resources within the nuclear family as the number of children grows, yet it fails to account for instances when the relationship between sibship size and education is often weak or even positive. To reconcile, we introduce a conditional resource dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 74 publications
2
79
0
Order By: Relevance
“…Both studies commonly found increasingly weaker negative associations between sibship size and education. For instance, the educational disadvantage associated with sibship size in the US nearly halved when comparing individuals born in the 1900s with those in the 1960s (Gibbs et al 2016). In line with this finding, Fahey (2017) also reported a steady decline in sibship size during the latter half of the twentieth century, particularly in the 1970s and 1980s, highlighting that the decline was most prominent among child with lower socioeconomic status, especially black children.…”
Section: Temporal and Societal Variations In The Relationship Betweenmentioning
confidence: 85%
See 3 more Smart Citations
“…Both studies commonly found increasingly weaker negative associations between sibship size and education. For instance, the educational disadvantage associated with sibship size in the US nearly halved when comparing individuals born in the 1900s with those in the 1960s (Gibbs et al 2016). In line with this finding, Fahey (2017) also reported a steady decline in sibship size during the latter half of the twentieth century, particularly in the 1970s and 1980s, highlighting that the decline was most prominent among child with lower socioeconomic status, especially black children.…”
Section: Temporal and Societal Variations In The Relationship Betweenmentioning
confidence: 85%
“…For example, using data from multiple US surveys, Blake (1989) assessed the relationship between sibship size and years of education and how it varies over time. Gibbs et al (2016) also addressed the same issue with more consistent and recent data, General Social Surveys from 1972 and 2010. Both studies commonly found increasingly weaker negative associations between sibship size and education.…”
Section: Temporal and Societal Variations In The Relationship Betweenmentioning
confidence: 93%
See 2 more Smart Citations
“…The role of the sibship configuration, including aspects such as sibship size (i.e. the number of siblings) and birth order, for attainment processes throughout the life course has been studied since the 19 th century (Galton 1874) and remains a contentious issue today (Black et al 2010;Gibbs et al 2016;Härkönen 2014;Jacob 2011). Questions of whether and how sibship size and other aspects of the sibship configuration may shape individuals' life chances are important to address to understand the interplay between demographic processes and intra-and intergenerational processes of social stratification (Steelman et al 2002).…”
Section: Introductionmentioning
confidence: 99%